2015
DOI: 10.1016/j.pmatsci.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Defect-interface interactions

Abstract: Nanostructured materials contain an extremely high density of interfaces. The properties of these materials when exposed to extreme conditions of radiation dose, stress, deformation, or temperature are largely determined by defect-interface interactions. In this article, we review the present understanding of defect-interface interactions in single-phase and two-phase metal and oxide nanocomposites, emphasizing how interface structure affects interactions with point, line, and planar defects. We also review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
231
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(239 citation statements)
references
References 464 publications
(801 reference statements)
7
231
0
1
Order By: Relevance
“…Therefore, these facetted bubbles are further evidence of significant vacancy trapping by the grain boundaries and it is reasonable to assume similar efficiency for coincident trapping of helium. The difference in sink efficiencies of different grain boundaries can also be experimentally confirmed by the observation of denuded zones (a bubble-free region in the vicinity of a boundary) as the width of the denuded zone is directly proportional to the grain boundary sink efficiency [26]. In the current study, the regions around grain boundaries demonstrated inconsistent behavior with some being denuded and some only partially denuded.…”
supporting
confidence: 74%
“…Therefore, these facetted bubbles are further evidence of significant vacancy trapping by the grain boundaries and it is reasonable to assume similar efficiency for coincident trapping of helium. The difference in sink efficiencies of different grain boundaries can also be experimentally confirmed by the observation of denuded zones (a bubble-free region in the vicinity of a boundary) as the width of the denuded zone is directly proportional to the grain boundary sink efficiency [26]. In the current study, the regions around grain boundaries demonstrated inconsistent behavior with some being denuded and some only partially denuded.…”
supporting
confidence: 74%
“…Physical vapor deposited (PVD) multilayers of facecentered cubic (fcc) and body-centered cubic (bcc) metals have proven to be excellent model materials for studying interactions between solid-state interfaces and radiation-induced defects [1][2][3]. They have been especially fruitful for investigations of the nucleation, growth, and interaction of helium (He) precipitates at fcc/bcc interfaces [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Clustering of these defects can lead to the formation of more complex defect structures, such as vacancy loops, interstitial loops, voids, and bubbles, which all can potentially degrade the mechanical properties [3,4] of the irradiated material and ultimately cause failure [1]. To mitigate these detrimental effects, recent studies have investigated novel engineering materials with high densities of defect sinks, such as grain boundaries [5][6][7] or structural interfaces [8]. Grain boundaries are thought to act as defect sinks and, in particular, to enhance point defect annihilation by absorbing interstitials and then reemitting them back to recombine with nearby vacancies [9].…”
mentioning
confidence: 99%
“…The resistance of grain boundaries to bubble formation in the grain matrix was correlated to the formation of denuded zones near the grain boundaries, which is a function of grain boundary sink efficiency [8]. Experimentally, insight about grain boundary sink efficiency can be gained through examining denuded zone formation in the irradiated samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation